The analgesic effect of non-pharmacological interventions to reduce procedural pain in preterm neonates - Kao-Hsian Hsieh; Shu-Jen Chen; Pei-Chen Tsao; Chih-Chien Wang; Ching-Feng Huang; Chien-Ming Lin; Ya-Ling Chou; Wei-Yu Chen; I-Ching Chan (Elsevier, 2018)
Background: Painful procedures are unavoidable in the medical care of preterm babies. The unpleasant experience during the neonatal period may contribute to hyperalgesia and poor neurodevelopment outcome later. Seeking effective interventions to reduce pain are strongly indicated for these very small premature babies. The aim of this study is to investigate if instilling breast milk (BM) or dextrose water into oral cavity can reduce the procedural pain of heel stick for preterm babies. Methods: This is a prospective study; 20 premature neonates are enrolled. Each study case received heel stick 4 times. BM, 10% dextrose water (D10W), distilled water (placebo) and nothing (control group) were given one after the other in random order to the same patient before heel stick. Premature infant pain profile (PIPP) was used to assess the pain scores. The whole process consisted of 4 sections: a baseline period for 1 min, intervention period for 1 min, heel stick period for 20 s, and recovery period for 5 min. The primary outcome is to compare the PIPP scores in the 4 groups. Results: Totally 20 babies completed this study. Median gestational age was 32 weeks 2 days (26 weeks 4 days-35 weeks 6 days) and median birth body weight was 1596 g (766-2435 g). The median PIPP scores and interquartile range at each time period were listed in the context. There are significant differences between BM/control group at all time periods, between BM/placebo group at 30-60 s, 1-2 min, and 2-3 min, and between D10W/control group at 0-30 s, 30-60 s, 3-4 min, and 4-5 min. There are no significant differences between BM/D10W, D10W/placebo, and placebo/control groups at any time periods. Conclusion: Giving something with taste such as BM or D10W is safe and effective in reducing the procedural pain of heel stick in preterm neonates; BM is the priority.